A comparison of the pre-war and post-war status of public elementary classroom teachers in Ilocos Norte (1939-40 and 1953-54) - Caday, Carolina T. 1932- ([Quezon City University of the Philippines], 1955)
This is a comparative study of the pre-war and the post-war status of the public elementary classroom teachers in Ilocos Norte. The aspects of the teacher's status were investigated and compared according to the following: professional and civil service status of two groups of teachers, their difference in social status, and comparison of their incomes and expenditures in relation to the standard of living.
Bibliography: l. 93-94.
Thesis (M.Ed.)--University of the Philippines, 1955
Typewritten
Vita
Keywords: Teachers -- Ilocos Norte